Design and development of a double spiral antenna with an artificial magnetic conductor structure for hyperthermia treatment. Issue 12 (17th October 2022) - Sharma, Nitika; Kaur, Amanpreet; Khanna, Rajesh; Singh, Hari Shankar; Agarwal, Mayank
Abstract: A double spiral antenna with an artificial magnetic conductor (AMC) is designed, fabricated, and experimentally tested for hyperthermia treatment as a microwave power radiator. The proposed double spiral antenna has a compact structure, designed on an FR4 substrate with a thickness of 1.6 mm, and the dimensions of the proposed antenna is 32 × 32 × 3.27 mm 3 . The width and space between the spiral arms is 1.54 and inner and outer radius of the spiral is arm 1 and 12.82 mm. The antenna is fed by aperture feeding having dimensions of 16 × 14 mm 2 that enhances the antenna's bandwidth. Further, an AMC unit cell (as a reflector) is designed to enhance the proposed antenna's performance, which is designed on an FR4 substrate with a size of 16 × 16 × 1.6 mm 3 . The size of an AMC structure is optimized to 64 × 64 mm 2, consisting of 4 × 4 unit cells and placed at a 5 mm distance at the backside of a double spiral antenna, which enhances the directivity, and gain of the proposed antenna and also converges backfield in the forward direction. At a 5 mm distance, the AMC structure behaves as a reflector and converges all back field radiation in the required direction to make a directional radiation pattern which enhances the antenna's bandwidth and gain. The proposed applicator (antenna + AMC structure) is simulated with a heterogeneous phantom (112 × 112 × 86 mm 3 ), and the performance of the applicator is evaluated by using a specific absorption rate (SAR) in terms of penetration depth (PD) and effective field size (EFS) inside the phantom. The PD and EFS are improved when an AMC structure is placed at the backside of the antenna. Further, the proposed applicator is analyzed for the regular shape of the tumor inserted in the phantom, with the tumor size as 20 × 20 × 10 mm 3, located at 10 mm distance from the skin surface. The study of temperature distribution inside the phantom is also done when 2.5 W of power is applied to the applicator in a simulation environment, a temperature rise of the tumor that between the range of 41–45°C is observed, allowing the proposed antenna with an AMC structure to be a good choice for the hyperthermia treatment.